First Identification of Fig Virus A and Fig Virus B in Ficus carica in Italy - Serafina Serena Amoia; Michela Chiumenti; Angelantonio Minafra (Plants, 2023)
Extracts of double-stranded RNA from three fig cultivars from an Apulian (Southern Italy) germplasm collection were used for high-throughput sequencing and revealed the presence of two distinct, recently described closteroviruses. Sequences obtained from these Apulian isolates belong to fig virus A and fig virus B and cover 38 and 25% of their RNA genome, respectively. Primer sets designed on selected contigs confirmed the presence of each virus in infected plants. A close phylogenetic relationship, investigated in a fragment of HSP70h protein, occurs among these isolates and the reference genomes. A nucleotide divergence (ranging from 10 to 30% along the different genes) was observed among our isolates and the reference genomes. This is the first finding of these virus species in autochthonous fig accessions in Europe.